Daily Living Activity Improvement After William Flexion Exercise in Low Back Pain Patients - Nyoman Tri Karisma Dewa; Anak Agung Ayu Niti Wedayani; Mukaddam Alaydrus; Emmy Amalia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Low Back Pain (LBP) is a leading cause of functional limitation, often impairing Activities of Daily Living (ADL). Evidence regarding ADL outcomes following combination physiotherapy in Indonesian hospital settings remains limited. This study evaluated the effect of William Flexion Exercise (WFE) combined with physiotherapy modalities on ADL among LBP patients at Mataram University Hospital. A quantitative quasi-experimental one-group pretest–posttest design was conducted with 11 participants recruited through consecutive sampling. ADL was assessed using the validated Barthel Index and analyzed using descriptive statistics and the McNemar test. Before intervention, all participants (100%) were categorized as having mild dependence. After combination therapy administered twice weekly for four weeks, eight participants (72.7%) achieved independence, while three (27.3%) remained mildly dependent. Statistical analysis demonstrated a significant improvement in ADL following the intervention (McNemar, p = 0.008). These findings suggest that WFE combined with physiotherapy modalities may improve functional independence in LBP patients. However, the small sample size and absence of a control group limit causal inference and generalizability. Further randomized controlled studies with larger samples are recommended to confirm these findings.